Modified Hodge Test versus Indirect Carbapenemase Test: Prospective Evaluation of a Phenotypic Assay for Detection of Klebsiella pneumoniae Carbapenemase (KPC) in Enterobacteriaceae - Mathers, Amy J. (American Society for Microbiology, 2013)
The currently recommended phenotypic test for the detection of carbapenemase-producing members of the family Enterobacteriaceae is the modified Hodge test (MHT). However, the MHT lacks specificity. Here we demonstrate an alternative phenotypic test, the indirect carbapenemase test, for the detection of bla(KPC)-producing isolates that has specificity superior to that of the MHT for non-Klebsiella Enterobacteriaceae.